Sequential estimation of creatinine removal by a haemodialyser. Issue 12 (2nd December 2021) - Magalhães, Felipe Y.; Orlande, Helcio R. B.; Suassuna, José H. R.
Abstract : This work is focused on the transient analysis of a haemodialyser. The objective is to sequentially estimate the concentration of creatinine in the blood returning to the patient, by solving a state estimation problem with measurements of the outflow creatinine concentration in the dialysate. Simulated measurements containing Gaussian errors were used in the inverse analysis, which was based on the Sampling Importance Resampling (SIR) algorithm of the Particle Filter method. Accurate results reveal that this technique may possibly be used for online monitoring and control of the haemodialysis therapy.